Simulation of benthic microalgae impacts on water quality in shallow water systems, Corsica River, Chesapeake Bay - Tian, Richard; Cai, Xun; Cerco, Carl F.; Zhang, Joseph Y.; Linker, Lewis C. (Frontiers in Marine Science, 2024)
Eutrophication and hypoxia represent an ever-growing stressor to estuaries and coastal ecosystems due to population growth and climate change. Understanding water quality dynamics in shallow water systems is particularly challenging due to the complex physical and biogeochemical dynamics and interactions among them. Within shallow waters benthic microalgae can significantly contribute to autotrophic primary production, generate organic matter, increases dissolved oxygen consumption, and alter nutrient fluxes at the sediment-water interface, yet they've received little attention in modeling applications. A state-of-the-art modeling system, the Semi-Implicit Cross-Scale Hydroscience Integrated System Model (SCHISM), coupled with the Integrated Compartment Model (ICM) of water quality and benthic microalgae has been implemented in the Corsica River estuary, a tributary to Chesapeake Bay, to study benthic microalgae impact on water quality in shallow water systems. The model simulation has revealed a broad impact of benthic microalgae, ranging from sediment-water interface fluxes to water column dynamics, and the effects are observed from near-field to far-field monitoring stations. High-frequency variability and nonlinearity dominate benthic microalgae dynamics, sediment oxygen demand, and nutrient fluxes at the sediment-water interface. Resource competition and supply determine the spatial scope of benthic microalgae impacts to far-field stations and the whole estuary system. Our study shows that benthic microalgae is a significant factor in shallow water dynamics that needs adequate attention in future observation and modeling applications.